Penerapan Taksonomi Bloom Revisi : Studi Tentang Kemampuan Mencipta (C6) dalam Pembelajaran Fikih - Luluk Faridah (STIKes Ibnu Sina Ajibarang, 2024)
The revised Bloom's Taxonomy is a framework of thinking that is widely used in education to design learning objectives, assessments, and curricula. The revised taxonomy by Anderson and Krathwohl changes the classification from nouns to operational verbs, starting from low to high cognitive levels: remember, understand, apply, analyze, evaluate, and create. This study aims to analyze the application of creative ability (C6) in Islamic Jurisprudence learning at MI Nurul Qodim, especially in the context of implementing the Revised Bloom's Taxonomy. This study uses a descriptive qualitative approach with observation, interviews, and documentation techniques. The results of the study indicate that students' creative abilities in Islamic Jurisprudence learning have not yet developed optimally. This is due to the learning method that still focuses on basic concepts in textbooks and the limited experience of students in solving contextual problems. Lower-grade students are still dominant in playing, while upper-grade students begin to show their ability to argue and solve simple problems. Therefore, a more innovative and contextual learning approach is needed to hone high-level thinking skills, especially in the realm of creating (C6).